Herbivore control in connected seascapes: habitat determines when population regulation occurs in the life history of a key herbivore. Issue 8 (13th March 2018) - Boada, Jordi; Farina, Simone; Arthur, Rohan; Romero, Javier; Prado, Patricia; Alcoverro, Teresa
Abstract : Herbivore outbreaks often trigger catastrophic overgrazing events in marine macrophyte ecosystems. The sea urchin Paracentrotus lividus, the dominant herbivore of shallow Mediterranean seascapes, is capable of precipitating shifts to barrens when its populations explode. Paracentrotus lividus is found ubiquitously in rocky macroalgal communities and in sandy seagrass meadows of Posidonia oceanica, two of the most important subtidal habitats in the Mediterranean. We explored if habitat‐specific regulation across the principal stages of the urchin life cycle could help explain the persistence of these populations in connected mosaics. We measured each of three relevant ecological processes (i.e. settlement, post‐settlement survival and predation) across a wide stretch of the Mediterranean coast (ca 600 km). Our results show that habitat‐specific regulation is critical in determining urchin populations: each habitat limited urchin sub‐populations at different life stages. Settlement was never limiting; urchins settled at similar rates in both habitats across the coast. Post‐settlement survival was a clear bottleneck, particularly in seagrass meadows where no juvenile urchins were recorded. Despite this bottleneck in seagrasses, adult urchin populations were very similar in both seagrass and macroalgal habitats indicating that other processes (potentially migration) could be key in determining adult distributions across the mosaic. The fact that population regulation is clearly habitat‐specific suggests that sea urchin populations may be significantly buffered from bottlenecks in mixed seascapes where both habitats co‐occur. Sea urchin populations can therefore persist across the seascape despite strong habitat‐specific regulation either by maintaining reproductive output in one habitat or by migrating between them. By affording these regulatory escapes to habitat‐modifying species, patchy mosaics may be much more prone to herbivore outbreaks and a host of cascading effects that come in their wake.